Reliability of Educational Content Videos in YouTubeTM about Stainless Steel Crowns - Prabhadevi C. Maganur; Zaki Hakami; Ravi Gummaraju Raghunath; Sudhakar Vundavalli; Ganesh Jeevanandan; Yousef M. Almugla; Sanjeev B. Khanagar; Satish Vishwanathaiah (MDPI AG, 2022)
The purpose of the present study is to evaluate the quality and educational information provided on YouTubeTM about stainless steel crowns (SSC). Videos were searched for on YouTube TM using keywords related to stainless steel crowns in pediatric dentistry in the Google Trends application. A total of 52 videos were available. After exclusion criteria application, 22 videos were selected for the study for analysis. To classify the video content as high or low quality, a scoring system formed of seven parameters was used. For a global evaluation of the video quality, the video information and quality index were applied. Data obtained were analyzed statistically. Only a few videos explained the importance of SSCs. Most of the videos uploaded with a high number of likes were of low quality. Very few videos were of high quality. The content quality and educational quality of videos is poor and incomplete. None of the videos explained the need for the SSC and its benefits in pediatric dentistry.